A Failing Regional Power? Nigeria's International Status in the Age of Boko Haram. (2nd September 2017) - Ogunnubi, Olusola; Onapajo, Hakeem; Isike, Christopher
ABSTRACT: Given its population size, economic strength, military capability and foreign policy directions, in past years Nigeria has been considered a major regional power in Africa. Clearly, this makes the country relevant at international and global levels. However, its status as a regional power on the continent is increasingly being affected as a result of the notorious terrorist activities of Boko Haram. Once a major contributor to peacekeeping operations in Africa and the rest of the world, Nigeria found itself relying on the support of other African states, including smaller ones, to fight Boko Haram. Furthermore, a huge number of Nigerians are now refugees across West Africa, especially in Chad Republic, Niger Republic and Cameroon. In view of this development, this article analyses the implications of Boko Haram terrorism for Nigeria's contemporary status in the international arena. The authors argue that the instability created by the terrorist group and the government's failure to deal with it decisively and timeously dents Nigeria's credibility and legitimacy to assert its influence at sub-regional and regional levels.